Strategi Komunikasi Kepemimpinan Pada Era Digital - Daryl Januar Isya; Shoffan Nizomi Suparman; Taufik Hidayat; Ety Yuliaty; Arina Nur Farida; Amir Tengku Ramly; Musa Hubeis (Universitas Ibn Khaldun Bogor, 2021)
In this era of the millennial generation, the role of modern digital media is very important because of technological developments, leaders are required to understand and be sensitive to the use of media in the digital era and implement communication within the organization. Good leadership communication will ensure that each member of the organization can do their job well. Without a good and correct communication network, it is possible that all processes within the organization cannot run optimally.Becoming a good leader in the current and future millennial generation is a critical challenge. With the times, many leaders have emerged due to environmental demands and conditions that must understand technology. Social media itself refers to internet-based applications, including social networks, wikis, blogs, and so on, which allow the creation and sharing of user-generated content. With the existence of social media can directly change the way people run their social lives. This includes changing the way people interact in the office. A leader in an office or an institution must also be good at communicating and conducting public communication in addition to being an expert in using social media.Communication is a process by which a person or persons, groups, organizations, and societies create, and use information to connect with the environment and other people